2020
DOI: 10.1017/s1478951520001200
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention to improve palliative care knowledge among informal caregivers of cognitively impaired older adults

Abstract: Objective Lack of palliative care knowledge among caregivers may pose an access barrier for cognitively impaired older adults, who may benefit from the specialized care. Therefore, this study aims to examine the effectiveness of an educational intervention in improving palliative care knowledge among informal caregivers of cognitively impaired older adults. Method Using a one-group, pre- and post-test intervention design, this study implemented an individual, face-to-face educational int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although the effect size for palliative care literacy became large in both the early and late stage groups at 3 months, those in the late stage group showed an early effect at 1 month, suggesting that family caregivers of patients with early-stage cancer may need time to improve their knowledge, or perhaps that those facing late-stage breast cancer were more interested in improving their palliative care literacy. Previous interventions have been shown to improve palliative care literacy among laypeople and family caregivers (Hoerger et al, 2017; Kozlov et al, 2017; Noh et al, 2021); however, these interventions were “stand alone” interventions rather than part of a broader or cancer-focused SFM intervention. Family caregivers nationally report low knowledge of palliative care (Dionne-Odom et al, 2019) and are interested in prognostic information, including about incurable cancer (Applebaum et al, 2018; Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect size for palliative care literacy became large in both the early and late stage groups at 3 months, those in the late stage group showed an early effect at 1 month, suggesting that family caregivers of patients with early-stage cancer may need time to improve their knowledge, or perhaps that those facing late-stage breast cancer were more interested in improving their palliative care literacy. Previous interventions have been shown to improve palliative care literacy among laypeople and family caregivers (Hoerger et al, 2017; Kozlov et al, 2017; Noh et al, 2021); however, these interventions were “stand alone” interventions rather than part of a broader or cancer-focused SFM intervention. Family caregivers nationally report low knowledge of palliative care (Dionne-Odom et al, 2019) and are interested in prognostic information, including about incurable cancer (Applebaum et al, 2018; Kang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We categorized the dichotomous, age variable for simplicity (Altman & Royston, 2006), as commonly used previously (Lee & Lee, 2018; Matejkowski et al, 2014). Age 50 was selected as the cutoff to convert to two groups because those in later middle age are more likely to be involved in caregiving for older adults, including end-of-life care, therefore, more likely to be exposed to and consider end-of-life issues (Noh et al, 2021b). Furthermore, Blacks/African Americans have earlier onset of chronic/ serious illnesses and shorter life expectancy than the general population and may experience end-of-life issues earlier than in the conventional older adulthood (65+).…”
Section: Methodsmentioning
confidence: 99%
“…When professionals (M = 12.74, SD = 0.58) were compared to community members (M = 10.92, SD = 2.2), the scores were found to be significantly different (t (83.87), p < 0.001), which represent professionals are more knowledgeable of palliative care concepts as expected. A strength of this tool is that it has been used in various populations: the public in Jordan (Abuelzeet et al, 2023), cancer patients in Iranian (Atena et al, 2022), patients with neuroinflammatory disease (Ben-Zacharia et al, 2023), theorydriven role model stories in diverse older populations (Hoe et al, 2021), Latino community leaders (Johnson et al, 2022), cross-sectional survey of young adults (Mallon et al, 2021), public knowledge in Northern Ireland (Mcllfatrik, 2021), informal caregivers of cognitively impaired older adults (Noh et al, 2021), scoping literature review in the general public (Patel & Lyons, 2020), development and validation of the Palliative Care Attitudes Scale (PCAS-9) (Perry et al, 2020), and Asian populations (Shen et al, 2020). The PaCKS tool has not been implemented in any study focused primarily on teenagers; however, it has been found to be inclusive of this population.…”
Section: Palliative Care Knowledge Scale (Packs)mentioning
confidence: 99%